PREPARATION OF FINANCIAL STATEMENTS ON EXTRA-BUDGET FUNDS IN HIGHER EDUCATION INSTITUTIONS (Conferencea, 2024)
As a result of the implemented reforms, the budget organization was considered as a radical change in the sources of funding of higher education institutions, in particular, for the first time, 10 higher education institutions of the republic were transferred to a self-financing system, and as a result of the gradual transfer of about 40 other state higher education institutions to financial independence, their existing capabilities were reduced. Based on this, new opportunities were given to attract budget and non-budgetary funds. From this point of view, the structure, classification and proper organization of accounting of extra-budgetary funds in higher education institutions is one of the urgent issues.